STRATEGI KONTINUITAS BISNIS MELALUI ANALISIS SWOT PADA SENTRA UMKM BATU BATA DAN GENTING DI KABUPATEN LAMONGAN - Rusminah, Sani; Sayekti, Levia Inggrit; Taufik, Muhammad (STAI Darul Qalam Tangerang, 2023)
The problems faced by Micro Small Medium and Enterprises actors are still often related to the lack of a business strategy. A business requires tenacity, courage and good management and business strategy. The goal is that business actors can face all types of risks posed by these businesses. This study aims to identify a business continuity strategy with a SWOT analysis approach to formulate a strategy so that brick and tile centers are able to compete with similar business actors. This study uses qualitative research methods based on postpositiveism or enterpretive philosophy, used to examine the condition of natural objects (as opposed to experiments) where the researcher is the key instrument, data collection techniques are carried out by triangulation (combined), and the results of qualitative research emphasize more meaning of generalization. The result of this research is the development strategy of combining SO (Strenghts & Opportunities), WO (Weakness & Opportunities), ST (Strenghts & Threats) and WT (Weakness & Threats).